EFFECT OF PROBIOTIC ADMINISTRATION Bacillus subtilis BN Strain ON QUALITY OF CHICKEN EGGS - Huda, Khoirul; Siswara, Hamzah Nata; Aini, Lia Nur (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2023)
This reseacrh aims to find out the effect of probiotic administration of Bacillus subtilis BN Strain on shell thickness, white index and chicken yolk index. This research used 38-week-old layer laying hens as many as 24 heads, randomized into four treatments with eight replays. Treatment consists of P0 without the addition of probiotics, P1 with the addition of Bacillus subtilis BN Strain as many as 0.005 grams / kg of feed, P2 with the addition of Bacillus subtilis BN Strain as many as 0.01 grams / kg of feed and P3 with the addition of Bacillus subtilis BN Strain as many as 0.02 grams / kg of feed. Based on the analysis of statistical data, the Analysis Of Variance (ANOVA) test showed no noticeable difference (p>0.05) to the thickness of the shell, white index or egg yolk index. The results showed that the addition of probiotic Bacillus subtilis BN Strain as many as 0.005 grams/kg of feed, 0.01 grams/kg of feed and 0.02 kg/kg of feed had no noticeable effect on the increase in egg shell thickness, egg white index and egg yolk index.